The Surgical Options and Clinical Evidence for Treatment of Wear or Corrosion Occurring With THA or TKA - Engh, Charles A. (Clin Orthop Relat Res, 2014)
BACKGROUND: Wear and corrosion occurring in patients with hip and knee arthroplasty are common causes of failure leading to revision surgery. A variety of surgical approaches to these problems have been described, with varying efficacy. Polyethylene wear, metal-on-metal (MoM) hip bearing wear, and problems associated with modular taper corrosion are the areas of greatest clinical impact; results of revisions for these problems are likely to dictate a large portion of revision resources for the foreseeable future, and so they call for specific study. QUESTIONS/PURPOSES: We identified the most frequently reported procedures to treat hip polyethylene wear, knee polyethylene wear, MoM wear after THA, and modular taper corrosion and determined the timing and reasons these failed. METHODS: We performed systematic reviews of the published literature on the four topics using MEDLINE(®) and Embase in October 2013; searches were supplemented by hand searches of bibliographies. Prespecified criteria resulted in the identification of 38 relevant articles, of which 33 were either case reports or Level IV evidence. Followup was generally at short term and ranged from 0.2 to 8 years. RESULTS: The most frequently reported procedures for treating clinically important wear were a partial or complete revision. When treating polyethylene wear, the more frequently reported reasons for hip and knee rerevisions were loosening, continued wear, and instability. Soft tissue reactions were more common and occasionally extensive in patients with MoM or modular taper corrosion. Patients with soft tissue reactions had more complications and higher rerevision rates. CONCLUSIONS: Studies with longer followup and higher levels of evidence are needed to direct the treatment of wear and corrosion. When soft tissue damage secondary to MoM wear or taper corrosion is present, the results of treatment can be poor. There is an urgent need to better understand these two mechanisms of failure.